The Effect of Insulin Administration on Medication Adherence in Type 2 Diabetes Mellitus Patients with Neurological Complications - July; Rani Sauriasari; Nadia Farhanah Syafhan; Hadijah Tahir (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Medication adherence is essential to achieving controlled blood sugar in diabetic patients. Insulin generally provides better glycemic control but is considered painful and requires special techniques. Insulin administration in patients with neurological complications requires particular consideration because these complications can cause physical and cognitive barriers. Objective: This study analyses the effect of insulin administration on medication adherence in diabetic patients with neurological complications and the influence of various confounding variables (baseline characteristics, medical and medication history). Methods: This observational study was conducted with a cross-sectional design at a government hospital in East Jakarta from September 2021 to January 2022. The sample was type 2 diabetes mellitus patients with neurological complications who received antidiabetics for at least six months. The neurological complications include central nervous disorders (such as stroke) and peripheral nervous disorders (such as neuropathy). The independent variable was insulin administration, while the dependent variable was adherence, measured using subjective methods [Adherence to Refills and Medications Scale (ARMS)] and objective methods (Medication Refill Adherence (MRA) and HbA1c]. Results: Of 175 respondents, based on the three methods (MRA, ARMS, HbA1c), 13 respondents (7.4%) were adherent, namely one respondent (1.8%) in the insulin group and 12 respondents (10.1%) in the non-insulin group. Insulin administration affects adherence to antidiabetics by 0.123 times (95% CI: 0.015 - 1.024), or patients who use insulin have 87.7% lower adherence controlled by antidiabetic changes and the total number of medicines used. Conclusion: Insulin administration significantly affects medication adherence in diabetes mellitus patients with neurological complications.